Single‐ion conducting polymer as lithium salt additive in polymerized ionic liquid block copolymer electrolyte. Issue 18 (2nd March 2023) - Goujon, Nicolas; Mendes, Tiago; Barlow, Kristine J.; Kerr, Robert; O'Dell, Luke A.; Chiefari, John; Howlett, Patrick C.; Forsyth, Maria
Abstract: Herein, we describe the use of single‐ion conducting block copolymer (SIC) as an additional lithium salt additive to a ternary solid polymer electrolyte (SPE), consisting of a poly(styrene‐ b ‐1‐((2‐acryloyloxy)ethyl)‐3‐butylimidazolium bis(trifluoromethanesulfo‐nyl)imide) (S‐ImTFSI64‐16 ) block copolymer, a N ‐propyl‐ N ‐methylpyrrolidinium bis(fluorosulfonyl)imide (C3 mpyrFSI) ionic liquid (IL) and a lithium bis(fluorosulfonyl) imide (LiFSI) salt. For this purpose, the S‐ImTFSI64‐16 was substituted by a SIC, based on poly(styrene‐ b ‐((4‐styrenesulfonyl)(trifluoromethanesulfonyl)imide lithium salt)) (S‐STFSILi64‐16 ), at various molar ratios. The impact of the SIC concentration on the phase behavior and transport properties of the SPEs was investigated by means of differential scanning calorimetry, electrochemical impedance spectroscopy, and diffusion NMR. In addition, the electrochemical performance of the SPEs was assessed in lithium symmetrical cell at 50 and 80°C. Finally, the cycling performance of a selected SPE was also assessed at 80°C in a Li│NMC111 cell with capacity loading of 1.3 mAh.cm −2 at a C‐rate of 0.1 C. The Li│NMC111 full cell was able to deliver a stable capacity of 0.94 mAh.cm −2 after 20 cycles, corresponding to a capacity of 117 mAh.g −1 . These results demonstrates that PIL block copolymer—IL—salt composites represent a promising choice of electrolyte for the next generation of solid‐state high energy density lithium metal batteries. Abstract :